Hubungan Persepsi tentang Tugas Pokok dan Beban Kerja dengan Kemampuan Profesional Guru - Syamsudin Syamsudin (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2003)
This expost-facto study aimed at finding the correlation between the level of teachers’ professional ability with their perception of their main duty and work load. These teachers attended Special Education of S1 program in UNM Makasar. Data were taken from 58 teachers who were selected by using proportional random sampling and were analyzed using correlation and regression analysis. It was found that most of the teachers already had sufficient professional ability and there was significant correlation between perception toward the learning facilitators’ main duty and work load with the teachers’ professional ability.